RICE-HUSK AND CORN WASTE BIOCHARS IMPROVE RICE GROWTH UNDER LEAD STRESS - Syarifa Mayly; Ida Zulfida; Dora Silvia Dewi; Dafni Mawar Tarigan; Lamria Sidauruk; Farida Hariani; Benny Hidayat (Jurnal Al Ulum LPPM Universitas Al Washliyah Medan, 2026)
Lead (Pb) contamination in agricultural soils threatens rice production by reducing plant growth and increasing the risk of heavy-metal accumulation in edible tissues. Biochar has emerged as a sustainable soil amendment capable of immobilizing heavy metals while improving soil properties. This study evaluated the comparative effectiveness of rice-husk biochar and corn-residue biochar applied at rates of 0%, 10%, and 20% in reducing Pb availability and enhancing the early growth of upland rice (Oryza sativa L.). A factorial completely randomized design with three replications was employed under controlled pot conditions. Soil pH, residual Pb concentration, rice growth parameters, biomass production, root development, and Pb accumulation in plant tissues were measured and analyzed using analysis of variance followed by Duncan's Multiple Range Test at the 5% significance level. Biochar application significantly reduced soil Pb concentration, with the 20% application rate decreasing Pb by approximately 23% compared with the untreated control. A parallel reduction in Pb accumulation was observed in rice tissues, indicating lower Pb bioavailability. Root length increased markedly from 6.35 cm in the control to 16.50 cm at the highest biochar rate, while shoot length also improved significantly. Corn-residue biochar generally promoted greater root development and biomass production than rice-husk biochar, likely because of its higher concentrations of exchangeable potassium, calcium, and magnesium. Although soil pH increased following biochar application, the differences were not statistically significant, suggesting that Pb immobilization resulted primarily from adsorption, ion exchange, surface complexation, and mineral precipitation rather than pH modification alone. Overall, biochar application rate exerted a stronger influence on Pb immobilization than feedstock type, whereas biochar feedstock more strongly affected plant growth. These findings demonstrate that agricultural-residue biochars represent promising, low-cost amendments for mitigating Pb contamination and improving early rice establishment, although long-term field validation is required before practical recommendations can be made.